Fostering resilience through mentorship and game-based learning: a mixed methods trial of the STRYV365 trauma-informed school program - Meurer, John R.; Lumelsky, Paula; Chelius, Thomas H.; McGuire, Madison; Stoltenburg, Abbey; Bates, Garrett; Kosuri, Snigdha; Sheriff, Salma; Harvey, Tamera; Gundacker, Constance; Sparapani, Rodney; Antognoli, David; et al. (Frontiers in Developmental Psychology, 2026)
BackgroundAdverse childhood experiences (ACEs) can have long-term negative effects on emotional regulation, social skills, and academic performance. Social-emotional learning (SEL) interventions are crucial for fostering resilience and positive behaviors.ObjectiveThis study evaluates how the STRYV365 trauma-informed interventions, integrating emotional intelligence (EI) principles through coaching, physical activities and a video game, impacted students facing ACEs by fostering resilience, emotional regulation, and EI competencies.MethodsA clustered cross-over incomplete block factorial randomization trial was conducted in four Milwaukee schools, involving students in grades 5–10. Participants were assigned to four groups: peak team only, Brain Agents only, both interventions, or control. SEL outcomes were measured through surveys and qualitative data from focus groups and interviews.ResultsParents/caregivers consented to research participation of their children. Three hundred twenty-nine students assented to completing six surveys over four semesters with 57 students participating in focus groups and 68 in interviews. Twenty-nine teachers also completed focus groups. Based on qualitative findings, both peak team and Brain Agents led to improvements in self-awareness, self-management, relationship skills, and decision-making for students. Students reported enhanced emotional regulation and resilience. Qualitative findings highlighted improved coping strategies, optimism, and social connections. Teachers reported increased student engagement and emotional openness. Regression models of survey data showed peak team significantly improved emotional regulation (p = 0.04) and Brain Agents enhanced coping strategies (p = 0.03), with marginal synergy in co-delivery. Students exposed to adversity, particularly family incarceration, had lower self-awareness.ConclusionThis study demonstrates the potential to improve SEL outcomes among children experiencing adversity through trauma-informed coaching and educational video games. While peak team coaching significantly improved emotional regulation, the implementation of Brain Agents digital game encountered challenges with student engagement, indicating that its scalability depends on enhanced implementation strategies. These findings highlight the important role of EI in trauma-informed interventions for urban youth.